The Dynamic Impact of Immigration on Natives' Labor Market Outcomes : Evidence from Israel - Sarit Cohen-Goldner; Marco Daniele Paserman (Institute for the Study of Labor (IZA), 2004)
This paper studies the dynamic impact of mass migration from the Former Soviet Union to Israel on natives? labor market outcomes. Specifically, we attempt to distinguish between the short-run and long-run effects of immigrants on natives? wages and employment. The transition of immigrants into a new labor market is a gradual process: the dynamics of this process come from immigrants? occupational mobility and from adjustments by local factors of production. Natives may therefore face changing labor market conditions, even years after the arrival of the immigrants. If immigrants are relatively good substitutes for native workers, we expect that the impact of immigration will be largest immediately upon the immigrants? arrival, and may become smaller as the labor market adjusts to the supply shock. Conversely, if immigrants upon arrival are poor substitutes for natives because of their lack of local human capital, the initial effect of immigration is small, and the effect increases as immigrants acquire local labor market skills and compete with native workers. We empirically examine these alternative hypotheses using data from Israel?s Labor Force and Income Surveys from 1989 to 1999. We find that wages of both men and women are negatively correlated with the fraction of immigrants with little local experience in a given labor market segment. A 10 percent increase in the share of immigrants lowers natives? wages in the short run by 1 to 3 percent, but this effect dissolves after 4 to 7 years. This result is robust to a variety of different segmentations of the labor market, to the inclusion of cohort effects, and to different dynamic structures in the residual term of the wage equation. On the other hand, we do not find any effect of immigration on employment, neither in the short nor in the long run.
Keywords: J61; J30; J00; F22; J21; 330; immigration; labor demand; labor supply; segmented labor markets; Einwanderung; Beschäftigungseffekt; Lohnniveau; Arbeitsnachfrage; Israel